New Technologies in the Carrying Out Rational Antibiotic Treatment of Bacterial Respiratory Infections in Children - Ye.I. Yulish; O.Ye. Chernyshova; B.I. Krivuschev (Zaslavsky O.Yu., 2013)
The article deals with the methods of rational antibiotic treatment of bacterial (extra- and intracellular) respiratory infections in children with use of dispersible forms of macrolides.